2016
DOI: 10.1002/lary.26259
|View full text |Cite
|
Sign up to set email alerts
|

Treatment delay and facility case volume are associated with survival in early‐stage glottic cancer

Abstract: 4. Laryngoscope, 127:616-622, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 41 publications
3
83
2
Order By: Relevance
“…Six studies (46%) 10,33,3639 included all head and neck subsites, while 7 studies (54%) were subsite specific (5 oral cavity, 1 oropharynx, and 1 larynx). 19,22,3032,34,35 Four of the studies (31%) 22,31,33,36 did not define the rationale or methods for their definition of prolonged DTI, 4 (31%) 19,35,37,38 used calendar-based categorical definitions (eg, <30 days, 31–60 days), 3 (23%) 30,34,39 used cohort-based quartiles or medians, and 2 (15%) 10,32 used recursive partition analysis to determine an optimal DTI threshold. One study, which exclusively examined cancer of the oral cavity, suggested that DTI of less than 20 days was optimal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies (46%) 10,33,3639 included all head and neck subsites, while 7 studies (54%) were subsite specific (5 oral cavity, 1 oropharynx, and 1 larynx). 19,22,3032,34,35 Four of the studies (31%) 22,31,33,36 did not define the rationale or methods for their definition of prolonged DTI, 4 (31%) 19,35,37,38 used calendar-based categorical definitions (eg, <30 days, 31–60 days), 3 (23%) 30,34,39 used cohort-based quartiles or medians, and 2 (15%) 10,32 used recursive partition analysis to determine an optimal DTI threshold. One study, which exclusively examined cancer of the oral cavity, suggested that DTI of less than 20 days was optimal.…”
Section: Resultsmentioning
confidence: 99%
“…10 An association between delays in DTI and poorer oncologic outcomes was observed in 9 studies (69%). 10,22,3137 The delayed DTI threshold varied from more than 20 days to 120 days or more. The 4 studies that did not find an association between DTI and survival analyzed thresholds of 50 days or more (vs 24days or less), 45 days or more (vs 30 days or less), and more than 30 days (vs 30 days or less; analyzed in 2 studies).…”
Section: Resultsmentioning
confidence: 99%
“…The NCDB is a nationwide clinical surveillance resource data set that includes approximately 70% of all newly diagnosed malignancies in the United States from over 1,500 cancer programs, as previously described . The NCDB has been used in a number of studies to study treatment‐related outcomes in head and neck malignancies . This study was determined to be exempt from institutional review by the Yale Human Investigation Committee.…”
Section: Methodsmentioning
confidence: 99%
“…Studies in small, single‐institution cohorts have suggested that delays may adversely affect survival. However, this has not been shown in a national cohort and no national benchmarks exist …”
Section: Introductionmentioning
confidence: 92%
“…Other delays, such as delays between diagnosis and treatment initiation and between surgery and adjuvant treatment, have been associated with survival in some studies. However, the literature is inconclusive …”
Section: Introductionmentioning
confidence: 99%